Family and Developmental History of Individuals With Autism Spectrum Disorder: Importance of the Clinical Diagnostic Interview for Diagnosis in Adolescents. An Explorative Study - Waltereit, Johanna; Czieschnek, Charlotte; Albertowski, Katja; Roessner, Veit; Waltereit, Robert (Frontiers in Psychiatry, 2021)
Background: Diagnosis of autism spectrum disorder (ASD) can be made early in childhood, but also later in adolescence or adulthood. In the latter cases, concerns about an individual's behavior typically lead to consultation of a mental health professional (MHP). As part of the initial clinical examination by the MHP, a clinical diagnostic interview is performed, in order to obtain the patient's history, and may lead to the hypothesis of ASD. We were here interested to study family and developmental history as key parts of the patient's history. The aim of the study was to investigate empirical differences between adolescents with ASD and adolescent control persons in family and developmental history. Method: Clinical diagnostic interview items addressing family and developmental history were adopted from their regular use at several university hospitals and in leading textbooks. Parents of male adolescents with normal intelligence and an ASD diagnosis (n = 67) and parents of male adolescents without psychiatric diagnosis (n = 51) between the age of 12 and 17 years were investigated. Data were operationalized into three categories: 0 = normal behavior, 1 = minor pathological behavior, and 2 = major pathological behavior. Differences were analyzed by multiple t-test of two-way ANOVA. Results: Adolescents with ASD expressed a profile of items significantly differing from control persons. Comparison of significant items with the empirical ASD literature indicated robust accordance. Conclusions: Our findings support the importance and feasibility of the clinical diagnostic interview of family and developmental history for initiation of the diagnostic process of ASD in adolescents.